STRATEGIC PLANNING OF BUSINESS INTELLIGENCE OPTIMIZATION OF DIGITAL MARKETING CONTENT AT PT. SOKA CIPTA NIAGA USING BUSINESS MODEL CANVAS - Putri, Novianti Indah; Saputra, Yogi; Hamdani, Alfinur (Journal of Applied Information System and Informatic (JAISI), 2025)
Through implementation comprehensive methodology , research This analyzing digital marketing strategy of PT. Soka Create Commerce in digital marketing strategies in the industry halal fashion . SWOT analysis identifies strength in live streaming and education content , with focus on human resource and equipment limitations . PEST analysis shows How environment influenced by halal regulations that prevent and encourage style life healthy . Instagram performance shows improvement range by 81% with expansion significant geographic and segmentation audience aged 18-34 years . The Business Model Canvas presents a proposal for product fashion class above which is halal certified and has integrated multi- channel distribution . In conclusion , PT. Soka Create Commerce need continue transformation digital with focus on development human resources and technology capacity For optimize market opportunities and facing competition industry. Method Business Model Canvas can make effective company in design and implement knowledge business For increase performance achievement digital marketing content . With do SWOT analysis in comprehensive , business can identify the right strategy For increase Power compete , reduce risk , and take advantage of source available power . Strategies based on SWOT analysis can covers Power competition , diversification product , market expansion , optimization technology information , management risk , and adaptation business . SWOT analysis is very useful tool For help business identify factors key influencing performance them , develop a comprehensive and thorough strategy For growth , and develop decision more strategic effective [3]. PEST is analysis management strategic that identifies factor macro external influences business.